Informal Earnings and Domestic Production - the size of the shadow economy of the household. Case of Turkey - Jankiewicz, Jacek; Gunes, Armagan Aktuna; Gunes, Okay; Garsztka, Przemysław (Research Papers in Economics and Finance, 2025)
We performed our calculations to find out the value of domestic production and the size of the informal economy of the households. The dataset used in this estimation was obtained by matching the Turkey Time Use Survey of 2006 with the Household Budget Survey for the years 2007 to 2011. Informal earnings were measured using household budgetary declarations and the concept of full income (including monetary values of time use on non-market activities). In our analysis we use terms of extended incomes (i.e. monetary incomes with the informal earnings of households) and extended full incomes (i.e. monetary incomes and monetary time values including informal earnings). An important result is that an increase in domestic production yields a decrease in the size of the informal economy for the self-employed, but it is contrary in case of among wage earners. The average estimation of the size of the informal economy in Turkey decreased on average from 73.59% to 70.89% of GDP respectively for monetary and full expenditure for the years 2007-2011. Further deeper analysis is needed to analyse income inequality among wage earners and self-employed workers participating in informal activities.